Expenditure Composition, Fiscal Adjustment, and Growth in Low-Income Countries - Clements, Benedict (IMF Working Papers; Working Paper ;, 2002)
This paper assesses the effects of expenditure composition as well as fiscal adjustment on economic growth in a sample of 39 low-income countries during the 1990s. The paper finds that strong budgetary positions and fiscal consolidation are generally associated with higher economic growth in both the short and long terms. The composition of public outlays also matters: Countries where spending is concentrated on wages tend to have lower growth, while those that allocate higher shares to capital and nonwage goods and services enjoy faster output expansion. Expenditure composition, along with the size of the fiscal consolidation and initial fiscal conditions, affects the sustainability of adjustment. Initial fiscal conditions also have a bearing on the nexus between fiscal deficits and growth.